The Patriarchy System as the Trigger of Sexual Coercion in The Novel Moxie By Jennifer Mathieu - nurliati nurliati; Rosmiati Rosmiati; Adi Prautomo (Faculty of Letters Universitas Balikpapan, 2020)
This research analyses how the patriarchy system acts as the trigger of sexual coercion as reflected in the novel Moxie by Jennifer Mathieu. The objectives of this research are 1) to determine the forms of sexual coercion in the novel Moxie, and 2) to determine how the patriarchy system triggers sexual coercion in the novel Moxie. The researcher used Alison M. Jaggar’s radical feminism theory as the main theory and Smuts's and Smuts’ theory of sexual coercion as the supporting theory in analyzing the collected data. Jaggar’s radical feminism theory is used to analyze how the patriarchy system triggers sexual coercion while Smuts and Smuts’ theory is used to analyze the forms of sexual coercion. The research methodology of this research is qualitative descriptive; in which the relevant data were collected from the text found in the novel Moxie. This research resulted in direct coercion such as sexual harassment, intimidation, and rape as the form of sexual coercion found in the novel Moxie. This research also resulted in patriarchal ideology and patriarchal stereotypes being the triggers of direct coercion in a patriarchal society.